Hypobaric versus normobaric hypoxia: Same effects on postural stability? - Degache, F.; Larghi, G.; Faiss, R.; Deriaz, O.; Millet, G. (High Altitude Medicine & Biology, 2012)
Aims: To test the hypothesis that postural stability would be more affected during acute exposure in hypobaric (HH) than in normobaric (NH) hypoxia. Methods: In separate trials, 12 subjects stood on a posturographic platform for two successive 25.6 sec tests in three conditions: eyes open (EO), eyes closed (EC), and verbal dual task (DT). Ambient pressure in O2 was matched between HH and NH at 1700 and 3000?m, respectively. Results: Compared to NH, the length of Centre of Pression trajectory in Y-axis was increased (p<0.05) in HH for EO at 1700m, EC at 1700 and 3000m, and for DT at 1700m, whereas the variance of speed of CoP was decreased (p<0.05) in EO, EC, and DT at 1700?m. Compared to normobaric normoxia (NN; 400 m), the surface of CoP trajectory was increased (p<0.05) in HH in EO and EC at 3000?m. Conclusions: HH deteriorated postural stability in the antero-posterior plane, for the variance of speed and the surface of CoP in 3 conditions, whereas no difference was observed between NH and NN. These results suggest that hypobaria instead of hypoxia per se plays an important role to the altered balance classically reported in altitude.